2014
DOI: 10.1007/jhep01(2014)048
|View full text |Cite
|
Sign up to set email alerts
|

Lifshitz-sector mediated SUSY breaking

Abstract: We propose a novel mechanism of SUSY breaking by coupling a Lorentz-invariant supersymmetric matter sector to non-supersymmetric gravitational interactions with Lifshitz scaling. The improved UV properties of Lifshitz propagators moderate the otherwise uncontrollable ultraviolet divergences induced by gravitational loops. This ensures that both the amount of induced Lorentz violation and SUSY breaking in the matter sector are controlled by Lambda_HL^2/M_P^2, the ratio of the Horava-Lifshitz cross-over scale La… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…[24], where Hořava gravity is coupled to supersymmetric matter for which SUSY breaking is mediated by the Lorentz violations in the gravity sector. In this scenario, both the SUSY breaking and the Lorentz violations in the matter sector are controlled by the ratio ðM Ã =M p Þ 2 ; i.e., the suppression mechanism of Ref.…”
Section: Mixed-derivative Hořava Gravitymentioning
confidence: 99%
“…[24], where Hořava gravity is coupled to supersymmetric matter for which SUSY breaking is mediated by the Lorentz violations in the gravity sector. In this scenario, both the SUSY breaking and the Lorentz violations in the matter sector are controlled by the ratio ðM Ã =M p Þ 2 ; i.e., the suppression mechanism of Ref.…”
Section: Mixed-derivative Hořava Gravitymentioning
confidence: 99%
“…However, due to the Lorentz violation, other excitations with different speeds might exist, unless a mechanism is invented to prevent this from happening, for example, by assuming that the matter sector satisfies the Lorentz symmetry up to the Planck scale [83,84]. 3 In (2+1)-dimensions, observational constraints from the Cherenkov effects are out of question, so in principle the speed of the spin-0 gravitons can be smaller than that of light.…”
Section: Non-projectable Hl Gravitymentioning
confidence: 99%
“…Second, the breaking of LI can have significant effects on the low-energy physics through the interactions between gravity and matter, no matter how high the scale of symmetry breaking is [26]. Recently, it was proposed a mechanism of SUSY breaking by coupling a Lorentz-invariant supersymmetric matter sector to nonsupersymmetric gravitational interactions with Lifshitz scaling, and shown that it can lead to a consistent Hořava gravity [27] 1 . Another scenario is to go beyond the perturbative realm, so that strong interactions will take over at an intermediate scale (which is in between the Lorentz violation and the infrared (IR) scales) and accelerate the renormalization group (RG) flow quickly to the LI fixed point in the IR [31][32][33].…”
Section: Introductionmentioning
confidence: 99%